Penerapan Model Pembelajaran Project Based Learning untuk Meningkatkan Keterampilan Menulis Pantun Siswa Sekolah Dasar - Rohimah, Helma (Papanda Publisher, 2023)
Pantun writing skills are needed to train students' literary writing skills from an early age. Pantun writing skills require good vocabulary processing, especially when making sampiran and the content must pay attention to rhyme (sound equations). PjBL is one of the innovative learning models, where learning is more student-centered, using projects as learning media.. Several studies have shown that PjBL can improve the poetry writing skills of elementary school students. The method of writing this scientific paper is to use a literature study (library research). The results of the research are expected to provide an overview to develop further research on the project based learning model and be integrated into other learning.